Composite salt corrosion deterioration characteristics and damage calculation models of concrete incorporated with corrosion inhibiting admixtures. (December 2021) - Meiyan, Hang; Minghui, Jiang; Wenlei, Zhao; Yubin, Yang; Teng, Cheng; Hao, Wang
Abstract: This research investigation was an experimental study which was intended to verify the corrosion deterioration characteristics of C30 concrete incorporated with different dosage amounts of corrosion inhibiting admixtures (abbreviated as CIA in this study) under the environmental conditions of composite salt corrosion. Damage calculation models were proposed for the purpose of evaluating the influencing effects of the different dosage amounts. The experimentation results showed that when the content of CIA was 5%, the compressive strength of the concrete could be effectively improved. In addition, the average penetration depth and migration coefficient of the chloride ions, along with the macrocell current of the rebars, could be decreased. At the same time, the mass loss rates, relative dynamic elastic modulus losses, accumulative damage, and internal pore quantities of the examined concrete specimens incorporated with 5% CIA were observed to be significantly lower than those of ordinary concrete samples during every freezing-thawing cycle. Furthermore, the degree of anti-corrosion deterioration of the concrete was significantly promoted. This study's established chloride ions permeability models, rebars corrosion model, and concrete freezing-thawing damage models, were found to have the ability to more accurately reflect the variations of various performance indexes of the concrete in composite salt erosion environments. Therefore, it was considered that the established damage models could potentially provide valuable guidance for forecasting the life expectancy of concrete in the future. Highlights: CIA could effectively improve the compressive strength of concrete. CIA could effectively improve the resistance of concrete to chloride ion penetration. CIA showed the ability to effectively inhibit the corrosion damages of the rebars. CIA could significantly improve the freezing-thawing resistance of concrete. Test of porosity analysis showed CIA could reduce the internal pores of concrete.